Coenzyme Q10, carotenoid, tocopherol, and retinol levels in cord plasma from multiethnic subjects in Hawaii. (September 2013) - Franke, A. A.; Lai, J. F.; Morrison, C. M.; Pagano, I.; Li, X.; Halm, B. M.; Soon, R.; Custer, L. J.
Abstract Coenzyme Q10 (Q10), carotenoids, tocopherols, and retinol are the major circulating lipid-phase micronutrients (LPM) known to help mitigate oxidative damage and prevent chronic diseases. However, the functions of these compounds in newborns are little understood. This is due, in part, to the paucity of studies reporting their concentrations in this population. We measured Q10, carotenoids, tocopherols, and retinol in cord plasma from 100 multiethnic subjects living in Hawaii using HPLC with diode array and electrochemical detection. Appropriate internal standards were used including, for the first time, custom designed oxidized (UN10) and reduced (UL10) Q10 analogues. These compounds reflected the oxidation of UL10 to UN10 that occurred during sample processing and analysis and thus permitted accurate adjustments of natively circulating Q10 levels. All LPM measured were much lower in cord than in peripheral plasma. Cord plasma levels of total carotenoids, tocopherols, and retinol were approximately 10-fold, 3- to 5-fold and 1.5- to 3-fold lower than those in children or women. Cord plasma levels of total Q10 (TQ10; median, 113 ng/mL) were approximately 2-fold or 7- to 9-fold lower than peripheral plasma levels of neonates or children and adults, respectively. In contrast, the UN10/TQ10 ratio was substantially higher in cord (24%) than in peripheral plasma of children (3–4%) or adults (9%). Among the 5 ethnic groups in our cohort, no differences were observed in the levels of UN10, UL10, or TQ10. However, significant differences in many of the LPM were observed between ethnicities. More research is needed to explain these phenomena.